Effect of fibre spinning conditions on the electrical properties of cellulose and carbon nanotube composite fibres spun using ionic liquid as a benign solvent - C. Zhu; S. S. Rahatekar; J. Chen; K. K. Koziol; J. W. Gilman; P. C. Trulove (eXPRESS Polymer Letters)
The aim of this study was to develop electrically conductive fibres from cellulose. To achieve this, the effect of fibre extrusion speed and fibre winding speed on the degree of alignment of multiwall carbon nanotubes (MWNTs), as well as the resulting electrical properties of the cellulose/MWNTs composite fibres were systematically studied. 1-Ethyl-3-Methylimidazolium Acetate (EMIMAc) was used as an environmentally benign solvent for dissolution of cellulose as well as for dispersion of MWNTs in the solution dope. To achieve good dispersion of MWNTs in the cellulose solution dope, MWNTs were non-covalently functionalized using carboxymethyl cellulose (CMC). This significantly improved the dispersion of MWNTs in the solution dope. The degree of alignment of MWNTs after both fibre extrusion and winding, was studied using scanning electron microscopy (SEM) and wide angle X-ray diffraction (WAXD). The degree of alignment of MWNTs was correlated with the electrical properties. A significant decrease in electrical conductivity accompanied the increase in degree of alignment of MWNTs when fibres were spun with higher extrusion speed. The decrease was also measured when fibres were spun with higher winding speed using a constant extrusion speed. However, the decrease in conductivity due to winding was low relative to fibres spun at highest extrusion speed.